Enabling a rapid SnO₂ chemical bath deposition process for perovskite solar cells - Tay, Darrell Jun Jie (2023)
Chemical bath deposition (CBD) is a common method to fabricate SnO2 electron-transport layers in perovskite solar cells. However, this typically requires long deposition times, a significant drawback for eventual commercialisation of perovskite solar cells. By applying ultrasonication during the chemical bath deposition process, higher rates of heterogenous nucleation were triggered which accelerated the CBD process without sacrificing coverage. Deposition times of 15min, 30min and 45min were investigated, and 30 minutes was determined to be the optimal duration for ultrasonication-assisted chemical bath deposition, with the current parameters.